The Detective as (Academic) Interpreter: A Reconsideration of Murder by Death - Álvarez Castaño, Emilio José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Murder by Death is a parody of mystery films which also criticizes the character of the detective, both in terms of his/her personal traits and his/her investigation methods. The similarities between the detective and the academic researcher invite to check how this criticism can also be applied to the latter.